Risk Cause Analysis On E-Procurement Bidding - Lily Kholida; Bismar Arif (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The current procurement of goods and services refers to the Electronic Procurement Service (E-Procurement) system in accordance with Presidential Regulation No.16 of 2018, however in its implementation the contractors still need adjustments. One of them is the contractor involved in the case study of this research which has failed in several tenders. This can create risks associated with value and profitability of the company. This study aims to cover this gap by knowing the risk factors for failure, level and the form of handling carried out by distributing questionnaires to the related contractors. Design/methodology/approach: Data analysis was performed using statistical software and the value was mapped using the Risk Relative Importance Index (RRI). Findings: The result show that the capacity of the bid files to upload is too large and there is no supplier support, are in moderate risk levels with scale respectively of 8,836 and 7,407. Problematic internet signal factors and incomplete design maturity levels are in high risk levels with a scale of 11.868 and 12.586. Meanwhile, the extreme risk level, namely the price cannot compete with other participants and the very limited time for calculating the tender, on a scale of 12,586 and 15,339 are factors that need attention.